Food Safety Traceability Technology Based on Block Chain - Hao, Miao; Tao, Heng; Huang, Wei; Zhang, Chengmei; Yang, Bing (Big Data Analytics for Cyber-Physical System in Smart City, 2021)
With the emergence and widespread application of intelligent technologies such as the Internet of Things and big data, many researchers have also begun to combine emerging technologies with food traceability systems. These studies have made innovations in data query and reading platforms or related encryption technologies. However, in traditional food traceability systems, data management information is still scattered, difficult to share, and difficult to trace. The purpose of this article is to study the food safety traceability technology based on blockchain technology. Based on the theoretical basis of blockchain technology, this paper proposes a traceability scheme formed by the combination of reverse search and recursive algorithm. Finally, this paper designs and implements a food safety traceability system. The experimental results show that the scheme proposed in this paper is more efficient than traditional traceability models. And by testing the performance of the system, the test results show that the system can meet the demand. In this paper, through testing the traceability rate of different schemes, the traceability rate of the scheme proposed in this paper is stable at about 1000 ms.